Effect of Entrepreneurship Education on Entrepreneurial Intention among University Students - Abdullahi, Mohammed Sani; Khalid, Nadeem; Ahmed, Umair; Ahmed, Elsadig Musa; Gumawa, Alhassan Musa (Journal of Technical Education and Training, 2021)
The aim of this study is to investigate the effect of entrepreneurship education (EE) through attitude toward behaviour (ATB), subjective norm (SN) and perceived behavioural control (PBC) on Entrepreneurial intention (EI) among University students in Nigeria. The study unit of analysis comprises of students from the three public universities in Kano State, Nigeria, namely, Yusuf Maitama Sule University Kano (YUMSUK), Bayero University Kano (BUK), and Kano University of Science and Technology (KUST) Wudil that participated in entrepreneurship education programme (EEP) in 2017/2018 academic session. A questionnaire was used to collect data from the 345 target respondents while correlation and regression analysis was used as the data analysis method to test the study hypotheses. The findings revealed that attitude toward behaviour (ATB) and subjective norm (SN) have a significant effect on EI while perceived behavioural control (PBC) has no significant effect on EI. The study suggests that university management should capitalize on EEP as a vehicle to improve student’s attitudes towards EI. The study contributes to the literature by investigating the effect of EE on EI among University students in Nigeria. The study is one of the few studies that was conducted in Northern Nigeria, particularly in the three public universities in Kano State. Thus, the findings of this study act as a strategic tool for university management to design their institutional policies in a way that captures an early phase of offering EEP to create knowledge of entrepreneurship for students in order to sharpen their attitude toward behaviour and subjective norm toward EI.